DESAIN INOVATIF KERAMIK KASONGAN MEMASUKI PERSAINGAN PASAR GLOBAL - Moh. Rusnoto Susanto (Faculty of Humanities, Jember University, 2012)
The principal aim of this study was to determine and measure the effectiveness of the innovative design development at the Center Ceramics / Pottery Kasongan in the context of the development of the creative industries to enter global market competition. Type a descriptive qualitative study used reflexively to description entire visual data and statistics accurately related to all aspects of the scope of the study as a result of detailed fieldwork and comprehensive. The research instrument used structured interview techniques and triangulation test on the development of design innovation and influence with global market absorption. Design development process in the industrial pottery Kasongan generally adopted local elements and adapted many aspects of modern and contemporary artistic needs. The trend observed-observe, imitate or adopters, and add a touch of creativity or new as a measure of artistic innovation is increasingly rising to serve the demands of the global markets. Thus the movement of the economy based on the orientation of the creative economy moving forward in realizing the government’s program to empower the creative industry centers are independent and brave creative economy to compete with other developed countries. Keywords: Sentra Industri Keramik Kasongan, exploration of innovative design, creative industries and global market competition